Cover Feature: Sulfonic Acid Functionalized Ordered Mesoporous Silica and their Application as Highly Efficient and Selective Heterogeneous Catalysts in the Formation of 1, 2‐Monoacetone‐D‐glucose (ChemCatChem 24/2018). Issue 24 (27th December 2018) - Krishna, Nunna V.; Anuradha, Sankaran; Ganesh, Reddi; Kumar, Velisoju V.; Selvam, Parasuraman
Abstract : The Cover Feature shows sulfonic acid functionalized ordered mesoporous silica (RSO3 H‐OMS) as catalyst for the acetonation of D ‐glucose. In their Full Paper, N. V. Krishna et al. demonstrate that the selectivity of this catalytic transformation can be altered by tuning the acidity of the catalyst, which depends on the nature and number of silanol groups on the surface of OMS used for grafting. More information can be found in the Full Paper by N. V. Krishna et al. onpage 5610 in Issue 24, 2018 (DOI:10.1002/cctc.201801462 ).